Large volume was associated with increased risk of acute non-hematologic adverse events in the hybrid of intracavitary and interstitial brachytherapy for locally advanced uterine cervical cancer: preliminary results of prospective phase I/II clinical trial. (25th April 2022) - Murakami, Naoya; Watanabe, Miho; Uno, Takashi; Sekii, Shuhei; Tsujino, Kayoko; Kasamatsu, Takahiro; Machitori, Yumiko; Aoshika, Tomomi; Kato, Shingo; Hirowatari, Hisako; Kaneyasu, Yuko; Nakagawa, Tomio; et al.
Abstract: Objective: This is the preliminary results of a multi-center prospective clinical trial evaluating the feasibility of the hybrid of intracavitary and interstitial brachytherapy for locally advanced cervical cancer. Methods: Patients with FIGO stage IB2, IIA2, IIB, IIIA, IIIB and IVA uterine cervical cancer pretreatment width of which was ≥5 cm measured by MRI were eligible. Protocol therapy consisted of 30–30.6 Gy in 15–17 fractions of whole pelvic radiotherapy concurrent with weekly CDDP, followed by 24 Gy in 4 fractions of hybrid of intracavitary and interstitial and pelvic radiotherapy with central shield up to 50–50.4 Gy in 25–28 fractions. The primary endpoint of phase I part was that the rate of grade ≥ 3 acute non-hematologic adverse events related to hybrid of intracavitary and interstitial would be <10%. Results: Between October 2015 and October 2019, 74 patients underwent primary registration, with 52 patients eventually proceeding to the secondary registration. The median pretreatment tumor width was 5.7 cm, and FIGO Stages were IB2 10, IIA2 2, IIB 20 and IIIB 20, respectively. The median high-risk clinical target volume D90 was 72.0 Gy (54.8–86.6 Gy, EQD2 ), rectum D2cc was 53.7 Gy (29.3–80.3 Gy) and bladder D2cc was 69.8 Gy (38.9–84.8 Gy). The rate of grade ≥ 3 non-hematologic adverse events related to hybrid of intracavitary and interstitial was 1.9% (1/52), and 17.3% (9/52) of patients experienced non-hematologic adverse events related to hybrid of intracavitary and interstitial of any grade. In multivariate analysis, high-risk clinical target volume ≥ 35 ml was associated with an increased risk of any grade of acute non-hematologic adverse events related to hybrid of intracavitary and interstitial ( P = 0.036). Conclusion: The feasibility and reproducibility of hybrid of intracavitary and interstitial were demonstrated from a multi-center prospective clinical trial. Abstract : The feasibility and reproducibility of hybrid of intracavitary and interstitial were demonstrated from a multicenter prospective clinical trial. High-risk clinical target volume ≥ 35 ml was associated with an increased risk acute non-hematologic adverse events related to hybrid of intracavitary and interstitial.